Correlation of Lower Third Molar Angulation and Posterior Space Discrepancy with Mandibular Anterior Crowding using 3d Intra Oral Scanner - Ayesha Iftikhar; Tayyaba Jahanzeb (Gandhara University, 2021)
OBJECTIVES: To objectively determine the correlation of lower third molar angulation and posterior space discrepancy with mandibular anterior crowding digitally using intraoral scanner. METHODOLOGY: Cross sectional analytical study conducted at Rehman College of Dentistry (RCD) Peshawar from15th November 2020 till 15th December 2020. Lower third molar angulation and posterior space discrepancy were measured by IC 3.1 measure software, using digital Orthopantomograms (OPG). Digitally scanned models by (CS 3600 intraoral scanner) were analyzed using (CS 3600 3D software).  Sample was divided into Control (N=30; perfect alignment), Experimental (N=30; crowding >1mm) groups, based on Little's Irregularity Index. Both lower third molar angulation and posterior space discrepancy (Ganss Ratio) were correlated with lower anterior crowding using Pearson's Correlation. To determine any difference between two groups independent t-test was used. RESULTS: Statistically insignificant difference and a weak correlation were found for Ganss ratio and third molar angulation in both control and experimental groups. CONCLUSION: Third molar angulation and the retro molar space has no direct effect on the lower anterior crowding.